A Study Teacher’s Directive Speech Act in Teacher Talk at SMP Muhammadiyah 1 Sleman - Syafitri, Meli (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aimed to describe the functions of directive speech acts used by the teacher at SMP Muhammadiyah 1 Sleman. The study utilized a descriptive qualitative approach, focusing on the directive speech acts of the English teacher. The researcher served as the primary instrument, involved in all stages of the research, including data collection via video recordings. Dialogues were transcribed and classified based on Bach and Harnish's theory of directive speech acts. Data analysis followed the interactive qualitative method by Miles and Huberman (1994). The result of this research finds that